Roasting and formaldehyde method to make bypass protein for ruminants and its importance: A review - KUMAR, SANJAY; KUMARI, RAJNI; KUMAR, KAUSHALENDRA; WALLI, T K (The Indian Journal of Animal Sciences, 2015)
Protecting highly degradable protein sources like GN cake and mustard cake by formaldehyde treatment gave very good results in terms of increased growth rate and milk production in cattle, buffaloes and goats. Several studies were conducted to prove this point. Higher protein degradability results in wastage of dietary amino acids as urea excreted through urine. With regard to soybean cake, its protein can also be protected through heat treatment, which reduces degradability of soya protein. Heat treatment of whole soybean also enhances its palatability and the heat also destroys the anti-nutritional factors contained in raw beans. Among the most notable of these factors is the protease inhibitor, which binds the digestive enzymes, trypsin and chymotrypsin, rendering it unavailable to the host animal. Thus, properly processed soybean is an excellent feed ingredient which can be incorporated in the ration for high yielding cattle, buffaloes and for growing calves. Roasting of soybean is the most common heat treatment given to this proteinous feed and the roasted soybean can be incorporated even in the complete feed blocks, to act as a concentrated source of energy and protein, for high yielding dairy cows producing 15 to 20 kg of milk / day. Formaldehyde treatment of cakes (GN cake, mustard cake and soybean cake) effectively reduces their protein degradability and feeding of such treated cakes improved performance of animals in terms of growth and milk production. The treated cake has no effect on the health of animals or the milk quality. The method is also low cost and feasible, the technology has gone commercial in India.